2019
DOI: 10.1080/09638288.2019.1610509
|View full text |Cite
|
Sign up to set email alerts
|

LEARN2MOVE 0–2 years, a randomized early intervention trial for infants at very high risk of cerebral palsy: family outcome and infant’s functional outcome

Abstract: f BOSK, Association of persons with a physical disability, Utrecht, The Netherlands ABSTRACT Purpose: To compare family and functional outcome in infants at very high risk of cerebral palsy, after receiving the family centred programme "Coping with and Caring for infants with special needs (COPCA)" or typical infant physiotherapy. Materials and methods: Forty-three infants at very high risk were included before 9 months corrected age and randomly assigned to one year COPCA (n ¼ 23) or typical infant physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(118 citation statements)
references
References 39 publications
2
104
1
11
Order By: Relevance
“…In contrast, the feasibility and preliminary efficacy trials of a novel parent coaching-based approach (COPCA) disappointingly did not confer any gains over and above passive neurodevelopmental therapy within traditional physiotherapy (yellow light, weak positive) [87][88][89][90]. Likewise, conductive education [91] and Vojta therapy [79,80] for infants with cerebral palsy also appear ineffective for improving movement skills (yellow light, weak negative).…”
Section: Early Interventionsmentioning
confidence: 98%
“…In contrast, the feasibility and preliminary efficacy trials of a novel parent coaching-based approach (COPCA) disappointingly did not confer any gains over and above passive neurodevelopmental therapy within traditional physiotherapy (yellow light, weak positive) [87][88][89][90]. Likewise, conductive education [91] and Vojta therapy [79,80] for infants with cerebral palsy also appear ineffective for improving movement skills (yellow light, weak negative).…”
Section: Early Interventionsmentioning
confidence: 98%
“…The authors reported that 22 infants (51%) were later diagnosed with cerebral palsy. 10,11 Again, the groups did not differ in developmental outcomes and the content of the physiotherapy was not associated with developmental outcomes. However, a difference in family function emerged and that was that the family's quality of life improved over time in the COPCA group, whereas it remained similar in the standard care group.…”
Section: Introductionmentioning
confidence: 86%
“…Both studies evaluated COPCA in infants at very high risk of cerebral palsy and used a double approach, by combining a randomised controlled trial (RCT) with process evaluation. The latter 8 included video recordings of the intervention sessions, in which distinguishable intervention elements were defined, quantified and analysed with respect to their association with developmental outcomes 6,9‐11 . The first study 6 comprised 46 term and preterm infants who had definitely abnormal general movements at 10 weeks of corrected age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we report the infant's neuromotor, cognitive, and behavioral outcome. In our accompanying article [11], we address family outcome and the child's activities and participation.…”
Section: Introductionmentioning
confidence: 99%